Who Influences the Influencer – First Approaches towards a Quantitative Influencer Marketing - Ronja Edler; Jens K. Perret (Research Journal for Applied Management (RJAM), 2021)
The present study revisits the topic of influencer marketing from a quantitative point of view. For a sample of 255 influencers from the field of women's fashion on Instagram the lists of those accounts they follow have been used to generate a network connecting them to their peers. Based on core metrics for the influencers in the sample and the network itself, two research questions have been considered. Asking for a relative measure of the relevance of an influencer among her peer group, it has been argued that a single metric alone does not suffice. Thus, the eigenvalue centrality as a measure of an influencer's relative importance in the network of her peers is proposed complemented by the betweenness centrality as a quantitative approximation of an influencer's reach. Both concepts are shown to focus on distinctly different concepts and are used to propose a two-dimensional approach to rank influencers. A secondary question regarding the clustering of influencers into national groups has been posed. While significant national clustering exists in the sample, so do links to influencers of different origins. Regarding cross-national links, it is particularly the highest ranked influencers that responsible for the major share of links. Nevertheless, the network of influencers in women's fashion clearly is of an internationally connected nature.
Keywords: 650; influencer; Instagram; women's wear; fashion; social network analysis; death of distance; social media